Лизанчук В., Рожик М. Історія російщення українців - Дзюба, С. (Сiверянський лiтопис, 2011)
Рецензія на книгу: Лизанчук В., Рожик М. Історія російщення українців. — Л. : ЛНУ імені Івана Франка, 2011. — 412 с.